Climate Change, Nutrition, and Bottom-Up and Top-Down Food Web Processes. (December 2016) - Rosenblatt, Adam E.; Schmitz, Oswald J.
Abstract : Climate change ecology has focused on climate effects on trophic interactions through the lenses of temperature effects on organismal physiology and phenological asynchronies. Trophic interactions are also affected by the nutrient content of resources, but this topic has received less attention. Using concepts from nutritional ecology, we propose a conceptual framework for understanding how climate affects food webs through top-down and bottom-up processes impacted by co-occurring environmental drivers. The framework integrates climate effects on consumer physiology and feeding behavior with effects on resource nutrient content. It illustrates how studying responses of simplified food webs to simplified climate change might produce erroneous predictions. We encourage greater integrative complexity of climate change research on trophic interactions to resolve patterns and enhance predictive capacities. Trends: When studying the responses of food web dynamics to climate change, shifts in resource nutrient content are frequently overlooked, although they generally occur along with shifts in consumer physiology and behavior Studying the simultaneous effects of both processes on food webs is necessary because they are interdependent and have the potential to produce ecological surprises Nutritional ecology (NE) provides a convenient organizing principle on which to build understanding of the interdependent nature of the two processes because NE allows one to track the macronutrient connections between trophic levels By integrating top-down (shifts in consumer physiology and behavior) and bottom-up (shifts in resource nutrient content) responses to climate change into one conceptual framework, we can improve the realism of climate change ecology experiments and predictive accuracy